Perancangan Tata Letak Fasilitas Gudang Box dan Packing dengan Pendekatan 5R di PT Adiwraksa Atyanta - Oktavianus Bhakti Winahyu Kristiyanto; Febrina Agusti; Brillian Nur Diansari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to redesign the layout of the box warehouse and packing area to make it more effective and efficient. The existing problems include suboptimal space utilization, inefficient material flow, and poorly organized work areas. The method used is Systematic Layout Planning (SLP) combined with the 5R approach (Sort, Set in Order, Shine, Standardize, Sustain). The results show that the proposed layout improves space utilization efficiency, streamlines material flow, and enhances workplace organization. Therefore, the implementation of SLP and 5R is proven to be effective in improving warehouse operational performance.